Sexual Imageries in Eliot2019;s the Waste land as Plato2019;s Critique of Immoral Art (Global Journal of Human-Social Science, 2019)
The paper attempts to make a critical analysis of The Wasteland which justifies Plato s belief about art Plato s concept of mimesis led to rejection of art and poetry as merely projection of sex anger and other bodily pleasures which has a harmful effect on the rational disposition of individual Eliot was not left behind and one step further to plunge into the wild waters of sexuality revealing a remarkable sexual encounters through imageries which are rarely accounted for curative effect to the crazy world Indeed these sexual imageries are presented in most horrible picture which surely intended to spoil and demoralize the minds of the youth
Keywords: mimesis; sexuality; rational disposition; imageries; demoralize; bodily pleasure